Synthesis, Characterization and Antibacterial Activity of Ln(III) Complexes with Unsymmetrical Schiff Base Ligand - Bi, Caifeng; Yang, Jun; Fan, Yuhua; Bi, Shuangyu; Zhang, Dongmei; Zhang, Xia (Asian Journal of Chemistry, 2011)
A new unsymmetrical tetradentate Schiff base (H2L) was synthesized using 5-chloro-2- hydroxybenzophenone, o-phenylenediamine and o-vanillin. Three Ln(III) complexes of this Schiff base with the general composition [Ln(HL) (NO3)2( H2O)]·2H2O (Ln = Er, Pr, Gd), have been prepared and characterized by elemental analyses, IR spectra, UV spectra, 1H NMR spectra, TG-DTG and molar conductance. The antibacterial activities of the ligand and its complexes are also studied. The antibacterial experiments indicate that the ligand and its complexes possess antibacterial activity against Escherichia coli, Staphylococcus aureus and Bacillus subtilis and that the complexes have higher activity than that of the Schiff base.